A study of strain-rate effect and fiber reinforcement effect on dynamic behavior of steel fiber-reinforced concrete. (15th January 2018) - Sun, Xiaowang; Zhao, Kai; Li, Yongchi; Huang, Ruiyuan; Ye, Zhongbao; Zhang, Yongliang; Ma, Jian
Highlights: SFRC of a large range of fiber content are compressively tested using SHPB facility. Wave-shaper technique is investigated and adopted through the experiment. Strain-rate effect and fiber reinforcement effect of SFRC are studied thoroughly. Mechanisms underlying the two effects and their coupling effect are investigated. Abstract: This paper presents an experimental study on uniaxial mechanical properties of steel fiber-reinforced concrete (SFRC) subjected to high strain-rate compressive loading. SFRC specimens of 6 different steel fiber volume fractions (0.0%, 0.75%, 1.5%, 3.0%, 4.5% and 6.0%) are fabricated and tested using a 75-mm-diameter split Hopkinson pressure bar (SHPB). Wave-shapers are investigated to ensure that two basic assumptions of SHPB hold true and that constant strain-rate is maintained within SFRC specimens. Based on acquired dynamic stress–strain relations, dynamic strength increase factor, fiber reinforcement factor, critical strain, and energy absorption are studied versus both strain-rate and fiber volume fraction. That provides an insight into strain-rate effect and fiber reinforcement effect on dynamic behavior of plain concrete and SFRC. The mechanisms underlying strain-rate effect and fiber reinforcement effect are discussed.